ROOTS, ORIGINS AND DEVELOPMENT OF RHYTHMIC GYMNASTICS: A HISTORICAL INSIGHT - Francois Johannes Cleophas; Una T. Visser (University of Ljubljana Press (Založba Univerze v Ljubljani), 2024)
Rhythmic gymnastics is a sport that was designed to be the more feminine sister discipline of women's artistic gymnastics. Its roots, however, are embedded in a male hegemonic European history that manipulated elements of dance, physiology and pedagogy. Key role players were François Delsarte, Émile Jaques-Dalcroze, Isadora Duncan and George Demeny who greatly influenced the development of rhythmic gymnastics. These individuals extended previous work of the earlier gymnastics pioneers - Johan Guts Muths, Ludwig Jahn and Per Ling. Since its inception as a competitive sport in the former Union of Soviet Socialist Republics during the 1940s, rhythmic gymnastics expanded greatly until it was officially recognised by the International Federation of Gymnastics (FIG) in 1962. In 1963, the first World Championship competition was held and the sport gained increased international traction. This study aims to investigate social and political factors that contributed to the development of rhythmic gymnastics, from its origins in the European systems up to its recognition as an independent sport in 1973. We conclude our article with the supposition that the sport did not directly challenge male hegemonic systems, but that women in this sport started shifting gender expectations and norms.